As relaç\~oes econômicas do Brasil com os principais Bancos Multilaterais de Desenvolvimento (1990-2012) - Carlos Eduardo Lampert Costa; Manuel José Forero González; Nathália Filgueiras de Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This paper aims to analyze the relationship between Brazil and major Multilateral Development Banks (MDB) between 1990 and 2012. For this purpose, three MDBs were considered, namely, the International Bank for Reconstruction and Development (IBRD, World Bank), the Inter-American Development Bank (IDB ) and the Andean Development Corporation (CAF), later renamed to Development Bank of Latin America. In order to obtain a better understanding about the working rationale of these international financial institutions, the paper begins by examining their operational and administrative procedures, as well as raising issues related to their strategies, products and financing conditions. More specifically, with regard to these three banks, the work analyzes the dynamics of loans and financial flows in sectorial, geographic and institutional terms. It also seeks to give an account of strategies implemented in accordance with Country Strategy Papers developed by each of these institutions. Since 1990, the volume of loans to Brazil grew significantly, totaling nearly USD 86 billion in the stated period, a result of long-standing partnerships that were able to resolve, mainly after the economic stabilization in 1994, several disagreements experienced before 1990, especially with the IBRD.
Keywords: O31; 330; development finance; multilateral development banks; international institution of financing